Metanolisis Minyak kelapa dengan Katalis Enzim Lipase dalam Bubuk Getah Pepaya (Carica Papaya Latex, CPL) - Sri Sukadarti; Siti Diyar Kholisoh (Eksergi, 2009)
This research was aimed to obtain an alternative way for manufacturing methyl ester which is cheaper with a quality that meets the standards. According to its availability and abundance in Indonesia, coconut palm oil was applied as the raw material and lipase enzyme in papaya latex was used as its catalyst.